Effect of Pressures and Durations of Cupping Therapy on Skin Blood Flow Responses - Wang, Xiaoling; Zhang, Xueyan; Elliott, Jeannette; Liao, Fuyuan; Tao, Jing; Jan, Yih-Kuen (Frontiers in Bioengineering and Biotechnology, 2020)
Cupping therapy has been widely used in treating musculoskeletal impairments. However, there is no specific guideline on selecting the intensity of cupping therapy, including the pressure and duration. The objective of this study was to investigate the effect of different pressures and durations of cupping therapy on skin blood flow responses. A 2×2 factorial design, including 2 negative pressures at -225 and -300 mmHg and 2 durations at 5 and 10 minutes, was tested in 12 healthy participants. The 4 protocols of cupping therapy were tested in 4 different days. Skin blood flow was measured using laser Doppler flowmetry on the left triceps (the SJ12 acupoint). Skin blood flow after cupping therapy was expressed as a ratio of skin blood flow before cupping therapy. The results showed that -300 mmHg caused a significant increase in peak skin blood flow (16.7±2.6 times) compared to -225 mmHg (11.1±2.2 times, p<0.05) under 5-minute duration. The largest difference in skin blood flow is between -300 mmHg for 5 minutes (16.7±2.6 times) and -225 mmHg for 10 minutes (8.1±2.3 times, p<0.01). Our findings demonstrated that a higher value (300 mmHg) of negative pressure is more effective on increasing skin blood flow compared to a lower value (225 mmHg). Also, a shorter duration (5 minutes) causes a larger peak and total skin blood flow compared to a longer duration (10 minutes). This study provides the first evidence showing the effect of pressures and durations of cupping therapy on skin blood flow responses.